STUDI KOMPARATIF TENTANG HUKUM WARIS ANAK BEDA AGAMA MENURUT ISLAM DAN KITAB UNDANG-UNDANG HUKUM PERDATA - NIM. A1011161028, NOVIANA SYAFLIANTI (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstrac This thesis discusses the position of heirs who have different religions with the heirs. The position of inheritance rights of different religions according to Islam lies in Article 171 letter c of the KHI, where in the article states that the heirs and heirs must be Muslim, while according to Civil law (BW) regarding the status of inheritance rights of children of different religions lies in Article 838 of the Civil Code, where in the article states that those who are not eligible to become heirs are those who are accused of murder, slandering the testator, having committed a crime with a sentence of five yejars in prison, committing violence, and also having embezzled, damaged, or falsified a will. So, in Civil Law (BW) different religions are not a barrier to someone becoming an heir. Because, according to Article 838 of the Civil Code, those who are entitled to become heirs are blood relatives, both legal and out of wedlock and the husband or wife who has lived the longest. The legal consequences of the occurrence of religious differences between the heirs and heirs can be seen that they get the same amount of rights as heirs who are of the same religion as the heirs. This is contrary to the provisions in Islamic law, that a person who is of a different religion with an heir who is Muslim is entitled to inherit property from the heir but not as an heir, but as a recipient of inheritance based on a mandatory will. The mandatory will is worth not more than 1/3 of the inheritance.The formulation of the problem in this study is